(untitled) (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Summary: Records of 9,200 infants born with meconium staining of the amniotic fluid in Abha Maternity Hospital, Saudi Arabia, during the period January 1985 to December 1997, were reviewed in order to compare the morbidity and mortality patterns in those receiving oropharyngeal as against those receiving intratracheal suctioning. Of this number, 6,050 (65.8 percent) were intubated for intratracheal suctioning while the remaining 3,150 (34.2 percent) were suctioned down to the oropharynx only. Regardless of the method of suctioning, the incidence of meconium aspiration syndrome (MAS) was the same (7 percent) in both groups. The consistency of the meconium, physical condition of the infant at birth, and whether the pharynx and vocal cords were meconium stained or not, did not appear to influence the frequency of MAS. However, morbidity as determined by the need for prolonged administration of oxygen (48,0 percent vs 79.4 percent) or mechanical ventilation (13.0 percent vs 39.9 percent) was comparatively less among the infants intubated for suctioning in the delivery room. Similarly, the frequency of pneumotho rax (7.8 percent vs 32.6 percent), persistent foetal circulation (5.0 percent vs 18.5 percent) and fatality rate (1.9 percent vs 10.3 percent) were less in those who were intubated. These find ings support the need for routine intubation for intratracheal suctioning in every meconium stained infant regardless of his condition at birth.